Myocardial salvage is reduced in primary PCI-treated STEMI patients with microvascular obstruction, demonstrated by early and late CMR. - Shanmuganathan Limalanathan; Jan Eritsland; Geir Øystein Andersen; Nils-Einar Kløw; Michael Abdelnoor; Pavel Hoffmann (PLoS ONE, 2013)
OBJECTIVES: This study evaluates the association between microvascular obstruction and myocardial salvage, determined by cardiac magnetic resonance performed both in the acute stage of myocardial infarction and after 4 months. METHODS: In patients with acute ST-elevation myocardial infarction treated by primary percutaneous coronary intervention, myocardial salvage, infarct size, left ventricular volumes, and ejection fraction were assessed by early (1-4 days) and follow-up (4 months) cardiac magnetic resonance. These variables were related to the presence or absence of microvascular obstruction at early investigation. Myocardial salvage was determined by: (1) myocardium at risk and infarct size measured in the acute stage and (2) myocardium at risk, measured acutely, and infarct size measured after 4 months. Multivariate analyses were performed, adjusting for clinical confounders at baseline. RESULTS: Microvascular obstruction was present in 49 of 94 included patients, (52%). Myocardial salvage was significantly reduced in patients with microvascular obstruction, compared to those without: 23% vs. 38%, measured acutely, and 39.8% vs. 65.4%, after 4 months (p<0.001). The presence of microvascular obstruction was significantly and independently associated with large infarct size, lower left ventricular ejection fraction, and larger left ventricular end-systolic volume. CONCLUSION: The presence of microvascular obstruction demonstrated by cardiac magnetic resonance early after infarction was associated with impaired myocardial salvage. This association was more marked when based on measurement of infarct size after 4 months compared to assessment in the acute stage.